Modeling potential impacts of future climate change in Mzimba District Malawi, 2040-2070: An Integrated Biophysical and Economic Modeling Approach - Gama, Arthur Chibwana; Mapemba, Lawrence; Masikat, Patricia; Tui, Sabine Homann-Kee; Crespo, Olivier; Bandason, Elizabeth (International Food Policy Research Institute, 2014)
This study investigates possible climate change patterns over the period 2040 to 2070 in order to assess the potential economic impacts for crop-livestock integrating and non-integrating farmers in Mzimba district in northern Malawi. Thirty year historical climate data were used with 20 Global Circulation Models (GCM) to generate plausible future climates. Future maize yields then were simulated using the APSIM crop model. The Trade-Off Analysis model for Multi-Dimensional Impact Assessment (TOA-MD) framework was used with the crop model results for economic analysis.